“Holding on to Hope”: follow up qualitative findings of a tobacco treatment intervention for people experiencing mental health conditions - Tessa-May Zirnsak; Kristen McCarter; Melissa L. McKinlay; Ashleigh Guillaumier; Nadine Cocks; Catherine Brasier; Laura Hayes; Amanda L. Baker; Donita E. Baird; Billie Bonevski; Ron Borland; Ron Borland; et al. (Frontiers in Psychiatry)
BackgroundMental health service users are more likely to smoke tobacco and are as likely to make quit attempts as people not experiencing SMI, but they are less likely to succeed. Quitting tobacco can be harder for people experiencing SMI due to higher levels of nicotine dependence, more severe withdrawal, and many other complex factors. The Quitlink study was a randomized controlled trial combining a tailored 8-week Quitline intervention delivered by dedicated Quitline counsellors plus combination nicotine replacement therapy for people who experience SMI. The purpose of this paper is to report on the medium- and longer-term findings from interviews conducted at 5 and 8 months.MethodsAs a part of the broader Quitlink study, participants were invited to qualitative interviews at 2, 5 and 8 months following recruitment, in line with quantitative follow-up time points. Interviews were conducted with 28 participants in the Quitlink trial (intervention group n = 12, control group n = 16). Interviews were transcribed and analyzed with a thematic analysis methodology using NVivo 12. Key themes were determined using inductive coding.ResultsSix key themes were identified. These included: internal/external attributions for tobacco smoking, social relationships and relapse, the role of hopefulness in quitting, the role of clinicians in initiating and maintaining a quit attempt, increasing cessation literacy, and efficacy of the study intervention. Overall, findings suggested that participants’ quit attempts were often precarious and vulnerable, but active support and feelings of social connectedness were key to supporting participants to initiate a quit attempt and maintain gains.ConclusionsPeople who experience SMI can make attempts to quit smoking tobacco with support from clinicians and social networks. Connectedness and hope are significant enablers of making and sustaining quit attempts.Trial registrationThe Quitlink trial was registered with ANZCTR (www.anzctr.org.au): ACTRN12619000244101 prior to the accrual of the first participant and updated regularly as per registry guidelines.